Trends and Correlates of Nonmarital Fertility in Kenya: Evidence from the 2008–2022 Demographic and Health Surveys - Ikamari, Lawrence (Tanzania Journal for Population studies and Development, 2026)
Nonmarital fertility is an increasingly important feature of fertility change in Sub- Saharan Africa. In Kenya, urbanization and expanded female education are reshaping fertility patterns. Despite this, however, evidence on the trends and correlates of nonmarital fertility remains limited. This study addresses this gap. The analysis draws on a pooledsample of 26,345 never-marriedwomen aged15–49 from the 2008–09, 2014, and 2022 Kenya Demographic and Health Surveys. Descriptive statistics were used to examine prevalence and trends, while logistic regression identified key correlates. The results indicate that nonmarital fertility increased from 29.9% in 2008–09 to 35.7% in 2022, representing a rise of 5.8 percentage points. The increase was more pronounced among urban women, those with primary or higher education, and residents of Nairobi, Eastern, and Central regions. In contrast, declines were observed among Muslim women and those in Nyanza and Northeastern regions. Nonmarital fertility was significantly associated with age, cohabitation, education, household wealth, employment status, unmet need for family planning, religion, place of residence, region, and survey period. In conclusion, nonmarital fertility in Kenya is rising amid delayed marriage and unequal access to reproductive health services. Policy responses should expand youth-friendly contraception, strengthen girls’ education, and target structural inequalities—especially among adolescents and unmarried women in high-prevalence and informal urban settings—while supporting context-specific interventions and further research on employment and regional disparities.